Case analyses for abnormal psychology learning to look beyond the symptoms - Osborne, Randall E.; Lafuze, Joan Esterline; Perkins, David V. (New York, NY Routledge, 2016)
"Case Analyses for Abnormal Psychology, second edition uses case studies to explore the etiology, biology, and dynamics of psychiatric disorders in the DSM-5. Readers will learn about the new classifications and treatments for disorders while simultaneously reading the personal history of each consumer both before and during the development of each case. Every case ends with a section on the particular disorder presented, as viewed from a biological perspective. This updated edition bridges advances in abnormal psychology and neuroscience in understanding mental illness."
1. Major perspectives and the assumptions each makes about human behavior -- 2. Case formulation interviews : the importance of critical thinking in the clinical process -- 3. Classification and diagnosis -- 4. The case of Ricky G : schizophrenia -- 5. The case of Barbara M : major depressive disorder -- 6. The case of Sally W : bipolar disorder -- 7. The case of Carl V : borderline personality disorder -- 8. The case of Margaret H : obsessive-compulsive disorder -- 9. The case of Jacob T : autism spectrum disorder -- 10. The case of Sarah O : bulimia nervosa -- 11. The case of Latisha Q : panic disorder -- 12. The case of Richard B : alcohol use disorder -- 13. The Case of Paula H : posttraumatic stress disorder -- 14. The case of Brighid C : dissociative identity disorder -- 15. Wrapping up the journey.
Includes bibliographical references (pages [215]-220) and index.
Keywords: Psychology, Pathological -- Case studies